In This Issue - David Briggs (ACHSM, 2020)
This special issue responds to publications arising from presentations at the 2020 CPCE Health Conference held in Hong Kong in January. The conference was conducted by the College of Professional and Continuing Education of the Hong Kong Polytechnic University in association with a number a number of organisations including the Centre for Ageing and Healthcare Management Research and our colleagues from the Hong Kong College of Health Service Executives. The theme of the conference was 'Ageing with Health and Dignity - Implications for Public Policy, Service Delivery Workforce, Technology and Financing'.....